2022
DOI: 10.1371/journal.pone.0273700
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Vibrio parahaemolyticus isolated from stool specimens of diarrhea patients in Nantong, Jiangsu, China during 2018–2020

Abstract: Vibrio parahaemolyticus is the leading cause of acute seafood-associated gastroenteritis worldwide. The aim of this study was to investigate the presence of virulence genes, biofilm formation, motor capacities and antimicrobial resistance profile of V. parahaemolyticus isolates isolated from clinical samples in Nantong during 2018–2020. Sixty-six V. parahaemolyticus strains isolated from stool specimens of diarrheal patients were examined. The PCR results showed that there were two tdh+trh+ isolates, four tdh-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…V. parahaemolyticus was able to form biofilms and attached to the surfaces of seafood [ 53 ]. Sun et al [ 54 ] found that V. parahaemolyticus isolated from stool specimens of diarrhea patients exhibited biofilm formation. All clinical V. parahaemolyticus isolates were biofilm producers.…”
Section: Resultsmentioning
confidence: 99%
“…V. parahaemolyticus was able to form biofilms and attached to the surfaces of seafood [ 53 ]. Sun et al [ 54 ] found that V. parahaemolyticus isolated from stool specimens of diarrhea patients exhibited biofilm formation. All clinical V. parahaemolyticus isolates were biofilm producers.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, all oyster samples from all four States tested negative for the tdh and trh genes using the MIRA-LFD, PCR, and qPCR assays. This suggests that V. parahaemolyticus isolated from the environments may be less pathogenic compared to clinically isolated bacteria [10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, all oyster samples from all four States tested negative for the tdh and trh genes using the MIRA-LFD, PCR, and qPCR assays. This suggests that V. parahaemolyticus isolated from the environments may be less pathogenic compared to clinically isolated bacteria [10][11][12][13]. 0/6 (0%) 0/6 (0%) 0/6 (0%) 0/6 (0%) 0/6 (0%) 0/6 (0%) B 0/6 (0%) 0/6 (0%) 0/6 (0%) 0/6 (0%) 0/6 (0%) 0/6 (0%) 0/6 (0%) 0/6 (0%) 0/6 (0%) C 2/6 (33.3%) 0/6 (0%) 2/6 (33.3%) 0/6 (0%) 0/6 (0%) 0/6 (0%) 0/6 (0%) 0/6 (0%) 0/6 (0%) D 3/18 (16.6%) 0/18 (0%) 3/18 (16.6%) 0/18 (0%) 0/18 (0%) 0/18 (0%) 0/18 (0%) 0/18 (0%) 0/18 (0%)…”
Section: Detection Of Tlh Trh and Tdh Genes From Oyster Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Almost all V. parahaemolyticus isolates exhibited multiple antibiotics resistances, especially to ampicillin and colistin ( Amalina et al, 2019 ; Mok et al, 2021 ; Sun et al, 2022 ; Zaafrane et al, 2022 ). Previously, two class 1 integrons, dfrA14 - bla VEB-1 - aadB and bla VEB-1 - aadB - arr2 - cmlA - bla OXA-10 - aadA1 , which are strongly associated with the resistance to multiple antibiotics such as ampicillin, ceftazidime and cefotaxime, were detected in V. parahaemolyticus ( Lei et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%